DISTRIBUIÇÃO DE LUTZOMYIA LONGIPALPIS (DIPTERA: PSYCHODIDAE) E INFECÇÃO NATURAL POR LEISHMANIA CHAGASI NA ILHA DE SÃO LUÍS-MA, BRASIL - Soares, Maria Regiane Araujo (2006)
Lutzomyia longipalpis is the main vector of Leishmania chagasi, etiológico agent of leishmaniose visceral American (LVA) that it is configured as one of the main problems of world-wide public health. This species, of ample geographic and primarily wild distribution, has demonstrated a great capacity in if adapting to some environments, over all in the neighborhoods or interior of domiciles in urban and periurbanas areas. In such a way, the transmission of the LVA started to reach urban centers of medium and great transport, being modified the profile epidemiologist of the illness, previously considered wild or intent in small agricultural localities. In Brazil the LVA has been informed in the regions Southeastern, Center-West, North and Northeast, being that the last one concentrates the majority of the cases. In the state of the Maranhão, from 1982, the illness assumed the urban character and has been registered surtos epidemic throughout last the twenty and five years, adding up to 2005, a total of 7.668 notified cases.